PERCEPTIONS OF ONLINE LECTURES FOR NEW STUDENTS AT UNIVERSITY OF MUHAMMADIYAH SUMATERA UTARA - Siregar, Eko Febri Syahputra; Lubis, Baihaqi Siddik; Batubara, Ismail Hanif (Universitas Muhammadiyah Semarang, 2021)
Online learning makes a difference to education in Indonesia. Learning, which usually takes place in classrooms, is now happening online. For new students, lecturing on campus is something new because they have just joined Higher Education. However, they also have not experienced face-to-face learning but are forced to do it online. This study aims to determine the views of new students towards online lectures. Researchers view this as very important to do to determine the activity of lectures and the level of student satisfaction in attending lectures and to eliminate the desire of students to stop attending. This study used a cross sectional survey method with a measuring instrument in the form of a questionnaire distributed via google form. The subjects in this study were 254 new elementary school teacher education students. The research results reveal that; 1) 87.8% of students attend lectures using internet data packages, and 11% of students use wifi; 2) The applications used during the covid-19 epidemic were through university e-learning totaling 232 students, Zoom 191 students, Google Meet 166 students, Whatsapp Group 151 students, Google Classroom 57 students and Microsoft Teams 9 students; 3) new students did not understand the material provided during the online lecture by 48.8%, 45.7% had enough to understand, 4.3% did not understand and very much understood 1.2%. Students enjoy lecturing online, but they hope that lectures will be conducted face-to-face, this is because they have not felt the climate of lecturing at the university since joining UMSU. The results of this study can be used as a basis for improving the implementation of online lectures and academic services in the Elemetary School Teacher Education.